Lipid Profiles of the Heads of Four Shrimp Species by UPLC–Q–Exactive Orbitrap/MS and Their Cardiovascular Activities - Yongqiang Zhu; Peihai Li; Ronghua Meng; Xiaobin Li; Yuezi Qiu; Lizheng Wang; Shanshan Zhang; Xuanming Zhang; Houwen Lin; Hongbin Zhai; Kechun Liu (Molecules, 2022)
Lipids are key factors in nutrition, structural function, metabolic features, and other biological functions. In this study, the lipids from the heads of four species of shrimp (Fenneropenaeus chinensis (FC), Penaeus japonicus (PJ), Penaeus vannamei (PV), and Procambarus clarkia (PCC)) were compared and characterized based on UPLC–Q–Exactive Orbitrap/MS. We compared the differences in lipid composition of four kinds of shrimp head using multivariate analysis. In addition, a zebrafish model was used to evaluate pro-angiogenic, anti-inflammatory, anti-thrombotic, and cardioprotective activities of the shrimp head lipids. The lipids from the four kinds of shrimp head had different degrees of pro-angiogenic activities, and the activities of PCC and PJ shrimp lipids were more significant than those of the other two species. Four lipid groups displayed strong anti-inflammatory activities. For antithrombotic activity, only PCC (25 μg/mL) and PV (100 μg/mL) groups showed obvious activity. In terms of cardioprotective activity, the four kinds of lipid groups significantly increased the zebrafish heart rhythms. The heart distances were shortened, except for those of the FC (100 μg/mL) and PJ (25 μg/mL) groups. Our comprehensive lipidomics analysis and bioactivity study of lipids from different sources could provide a basis for the better utilization of shrimp.